Implementation of national childbirth guidelines in Brazil: barriers and strategies - Jorge Otávio Maia Barreto; Maritsa C. Bortoli; Cézar D. Luquine Jr; Cintia F. Oliveira; Tereza S. Toma; Aline A. V. Ribeiro; Taís R. Tesser; Daphne Rattner; Avila Vidal; Yluska Mendes; Viviane Carvalho; Mônica Almeida Neri; et al. (Pan American Health Organization, 2020)
The present report describes the process and results obtained with a knowledge translation project developed in three stages to identify barriers to the Implementation of the National Guidelines for Normal Childbirth in Brazil, as well strategies for effective implementation. The Improving Programme Implementation through Embedded Research (iPIER) model and the Supporting Policy Relevant Reviews and Trials (SUPPORT) tools provided the methodological framework for the project. In the first stage, the quality of the Guidelines was evaluated and the barriers preventing implementation of the recommendations were identified through review of the global evidence and analysis of contributions obtained in a public consultation process. In the second stage, an evidence synthesis was used as the basis for a deliberative dialogue aimed at prioritizing the barriers identified. Finally, a second evidence synthesis was presented in a new deliberative dialogue to discuss six options to address the prioritized barriers: 1) promote the use of multifaceted interventions; 2) promote educational interventions for the adoption of guidelines; 3) perform audits and provide feedback to adjust professional practice; 4) use reminders to mediate the interaction between workers and service users; 5) enable patient-mediated interventions; and 6) engage opinion leaders to promote use of the Guidelines. The processes and results associated with each stage were documented and formulated to inform a review and update of the Guidelines and the development of an implementation plan for the recommendations. Effective implementation of the Guidelines is important for improving the care provided during labor and childbirth in Brazil.